(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Close of efficacy of commercial banks is a main driver near the economy and commercial banks themselves to vie by their counters in this economical worldwide market. In this study, technical competences of Nepalese commercial banks below intermediation method and profit-oriented method remained assessed for the passé of 2005 to 2010 by means of input-oriented Data Envelopment Analysis (DEA). We initiate that now positions of the global nasty of the practical competence, the intermediation method on condition that additional efficacy totals than profit-oriented method. Rivalry and original tools can all be aims that banks remain acting well as the in-between purpose. Relating the totals for dissimilar kind of the Nepalese commercial banks founded arranged possession if varied consequences. Beneath intermediation method, combined scheme banks remained new effective while civic area banks remained originate new effective below profit-oriented method. Once likening the separate banks, Nepal Arab Bank Limited and Standard Charted Bank Limited banks remained new effectual below the equally methods. In count, Agriculture Development Bank Limited, Kumari Bank Limited and Siddhartha Bank Limited remained slightly effective (more than 90%) solitary below intermediation method. The learning originate that the bank by effective below intermediation method fixes not continuously nasty that receipts well productivity act.